A new Boussinesq model for wave run-up on curved structures using Cartesian cut-cell grids - Zang, J; Ning, D; Liu, S; Liang, Q; Taylor, P; Eatock Taylor, R; Borthwick, A (2007)
This paper presents a new Boussinesq model for simulating non-linear water wave interaction with curved structures in shallow water making use of a Cartesian cut-cell grid, as an extension of previous work for the nonlinear shallow water equations (Liang et al. 2007). The Cartesian cut-cell technique is implemented within the Boussinesq model to permit accurate boundary-fitting for complex geometries in the numerical domain. In combination with Godunov-type shock capturing schemes, the numerical solver provides highly resolved solutions for a wide variety of problems, including steep-fronted shallow flows, strongly non-linear waves, and breaking wave interactions with curved coastal structures. Numerical simulations are compared with experimental measurements of focused wave group interaction with a vertical surface-piercing cylinder. Copyright © 2007 by The International Society of Offshore and Polar Engineers(ISOPE).